Modeling and Controller Design of a Magnetic-geared Double Rotor Motor - Cao Jiayong; Yao Chunzhe; Wang Jingsen; Ren Chao (Jixie chuandong)
The magnetic-geared double-rotor permanent magnet motor is fused permanent magnet brushless DC motor and field modulated magnetic gear,which is a kind of low speed and high torque direct drive motor. It has opened up a new idea for improving the motor efficiency and torque density. It is an urgent problem to be solved that establish the electromechanical dynamics model and high-performance control of the kind of component. It is intended to establish the electromechanical coupling dynamic analysis model,and grasp the law that is the influence of controller parameters for driving system performance. Starting from the principle of motor operation,the motor can be decomposed into a brushless DC motor that is equivalent to high speed rotor and armature,and a magnetic gear equivalently that to the double rotor assembly considering elastic effect. The two part is combined of high-speed rotor. The numerical model of the motor is built in MATLAB/Simulink,and the system is regulated by using the PID control. Although the simulation results show that although there are the problems of nonlinear and coupling in the system,the tuned PID control can make the system track the input signal and achieve comprehensive performance index well.